Embedding Formative Assessment and Promoting Active Learning - Swinbank, Elizabeth; Whitehouse, Mary; Millar, Robin (Scientia in educatione, 2017)
In this contribution we outline how the York Science project is using a ‘backward design’ approach to teaching science to students aged 11–14. We then present some examples of formative assessment tasks and show how simple selected-response questions can be modified to provide teachers with detailed information about students’ ideas. Finally we indicate how such tasks can help promote active learning.